Health risk related to radon in a thermal spa utilizing waters from Guarani aquifer - Bonotto, Daniel Marcos [UNESP]; Santos, T. O. (Wit Press/computational Mechanics Publications, 2007)
This investigation was carried out within the Parana sedimentary basin, Brazil, involved the sampling of groundwater and air, and was realized with the purpose of evaluating the radioactivity, due to radon gas, in a thermal spa utilizing the waters from Guarani (Botucatu-Piramboia) aquifer. The results reported here provide additional information relative to that of previous studies focusing on the presence of radionuclides in the aquifer, which have mainly characterized those belonging to uranium and thorium series decay, such as the uranium isotopes (U-238 and U-234), radium isotopes (Ra-226 and Ra-228), radon daughters (Bi-214 and Pb-214) and radon (Rn-222) itself the results obtained were compared with the maximum permissible concentration limits in air and drinking water defined by international standards, such as the guidelines for drinking water quality established by the World Health Organization. The possible processes responsible for the presence of radon in the aquifer were also considered in order to evaluate the data obtained.
Keywords: radon; air; groundwater; Guarani aquifer; thermal spa